STUDY OF THE BIOCHEMICAL CHARACTERISTICS OF GLYCOSYLATED RECOMBINANT XYLANASE - Kiribayeva, A.; Silayev , D.; Abdullayeva , A.; Ramankulov , Ye.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2022)
The main renewable source of energy and raw materials on Earth is plant biomass, most of which consists of plant cell wall polymers: cellulose, hemicellulose, and lignin. Hemicelluloses are divided into three main types: xylans, mannans and arabinogalactans. Xylan is the second most abundant carbohydrate in nature after cellulose. The specific enzymes that hydrolyze xylan into xylooligosaccharides and D-xylose are xylanases. Prospective xylanases are enzymes derived from bacteria and mycelial fungi. Bacterial xylanases are characterized by high unitary activity, and additional manose chains can significantly increase the stability of the enzyme protein globule. Obtaining a glycosylated variant of bacillary xylanase, which are known for their high specific activity, seems promising. The Bacillus sonorensis T6 xylanase gene was cloned and expressed in the yeast Pichia pastoris. The recombinant xylanase was isolated and purified. The biochemical characteristics of the glycosylated recombinant xylanase were studied. It was found that the recombinant xylanase had maximum activity at 47-50°C and pH 6.0. The Km, Vmax and Kcat values are 3.037 ± 0.362 (mg/ml), 667.8 ± 31 (units/mg) and 100.3 ± 4.6 (s-1), respectively. The unitary activity of the recombinant enzyme is 873.8 units/mg. The glycosylated recombinant xylanase was found to have high temperature stability and retained 47% activity after a 2-hour incubation at 55°C. In addition to temperature stability, recombinant xylanase showed high pH stability - 10 h incubation in buffers with pH 3-11 did not decrease the activity. The effect of metal ions, detergents, and organic solvents on the activity of recombinant glycosylated xylanase was studied. The high biochemical parameters of recombinant glycosylated xylanase from Bacillus sonorensis T6 suggest that this enzyme is promising for use in the biotechnology and food industry.